2021
DOI: 10.1186/s12886-021-01845-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of painless one-eye blindness on depression, anxiety and quality of life in glaucoma patients with a normal fellow eye

Abstract: Background For clinical practice it is important to evaluate and compare anxiety, depression and quality of life of glaucoma patients with painless one-eye blindness and a normal fellow eye to unaffected age-matched individuals from a similar environment. Methods Twenty-eight stable glaucoma patients (age, mean ± SD: 69.0 ± 13.3 years) with one normal and one painless blind eye, and 26 controls (age: 67.0 ± 14.0 years) completed the standard Hungar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…[ 5 ] Findings from various studies have shown that glaucoma is associated with low levels of psychosocial well-being characterized by a diminution in the individual’s perception of self and ability to function in the community and usually manifests as depression and/or anxiety. [ 6 7 8 9 10 ] Depressed people feel sad, empty, hopeless, worthless, and irritable with an aversion to activity. [ 11 12 13 14 ] Although anxiety is distinguished by feelings of precariousness and vulnerability, in severe cases, it comes with repeated apprehension and intense fear, which is incommensurate to the existing situation causing it.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Findings from various studies have shown that glaucoma is associated with low levels of psychosocial well-being characterized by a diminution in the individual’s perception of self and ability to function in the community and usually manifests as depression and/or anxiety. [ 6 7 8 9 10 ] Depressed people feel sad, empty, hopeless, worthless, and irritable with an aversion to activity. [ 11 12 13 14 ] Although anxiety is distinguished by feelings of precariousness and vulnerability, in severe cases, it comes with repeated apprehension and intense fear, which is incommensurate to the existing situation causing it.…”
Section: Introductionmentioning
confidence: 99%
“…And the study agrees with our findings because a lot of partici-International Journal of Clinical Medicine pants (58%) had extreme difficulties reading ordinary prints despite being educated. Glaucoma patients are more likely to experience anxiety, depression and feelings of hopelessness about their future, and their self-reported health assessment is reduced [28]. This could be attributed to a number of factors because according to this study, most glaucoma patients are uncertain about the source of income to buy their medication as most of them (60%) earned less than $200 per month and this makes them (66%) be worried most of the their life time thereby sending themselves into depression.…”
Section: Discussionmentioning
confidence: 99%
“…Немаловажное значение представляет собой потенциальный порочный круг, в котором потеря зрения при офтальмонейродегенерациях вызывает психологический стресс и тревогу, оказывающие влияние на холинергическую систему мозга, вызывая дальнейшую потерю зрения. Например, часто отмечается страх пациентов перед слепотой с течением времени, даже с хорошо зрячим единственным глазом [79]. В то же время известно, что холинергические нейроны участвуют в регуляции когнитивных функций, включая страх [80], а психический стресс может изменять холинергическую нейротрансмиссию в головном мозге, нарушая работу системы ацетилхолина, что приводит к тревоге [81].…”
Section: цебролюкс™ нф нейрофактор и когнитивные функцииunclassified